2009
DOI: 10.1038/nsmb.1642
|View full text |Cite|
|
Sign up to set email alerts
|

Structural and functional studies of the Ras-associating and pleckstrin-homology domains of Grb10 and Grb14

Abstract: Grb7, Grb10 and Grb14 are adapter proteins containing a Ras-associating (RA) domain, a pleckstrin-homology (PH) domain, a family-specific BPS (between PH and SH2) region, and a C-terminal Src-homology-2 domain. Previous structural studies showed that the Grb14 BPS region binds as a pseudosubstrate inhibitor in the tyrosine kinase domain of the insulin receptor to suppress insulin signaling. Here, we report the crystal structure of the RA and PH domains of Grb10 at 2.6 Å resolution. The structure reveals that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(117 citation statements)
references
References 40 publications
3
106
1
2
Order By: Relevance
“…However, most previous GRB10 studies have been conducted in immortalised cell lines in vitro and it is not clear what role GRB10 plays in modulating insulin sensitivity in vivo. Moreover, a recent study using crystallography demonstrated that GRB10 binds to the insulin receptor far too weakly to have any significant physiological effect on insulin action [18]. These results raise questions about the proposed role of the GRB10 protein in the development of skeletal muscle insulin resistance, at least via any effect on insulin receptor phosphorylation [16,17].…”
Section: Introductionmentioning
confidence: 46%
“…However, most previous GRB10 studies have been conducted in immortalised cell lines in vitro and it is not clear what role GRB10 plays in modulating insulin sensitivity in vivo. Moreover, a recent study using crystallography demonstrated that GRB10 binds to the insulin receptor far too weakly to have any significant physiological effect on insulin action [18]. These results raise questions about the proposed role of the GRB10 protein in the development of skeletal muscle insulin resistance, at least via any effect on insulin receptor phosphorylation [16,17].…”
Section: Introductionmentioning
confidence: 46%
“…The BPS domain interacts with the 14-3-3 protein, another protein scaffold with numerous protein partners, and BCL2L11, a proapoptotic scaffold protein required for normal immune function (18,19). The PH domain has the fewest interacting partners although it has been confirmed to bind phosphoinositides (PIs), critical components of the cell membrane that affect vesicle transport and cell signaling (20). This interaction is consistent with the requirement of the PH domain for Grb10 localization to the cell membrane.…”
Section: Grb10 Binding Partners Define Its Role In Developmentmentioning
confidence: 52%
“…The RA domain of Grb7 and Grb14 extensively interacts with Ras-GTPases, important regulators of intercellular signaling related to cell growth and vesicle transport (21). Grb10 has been confirmed to bind at least one of these GTPases, NRAS (20). Finally, the PR domain binds to GIGYF1/2, proteins that are implicated in the modulation of insulin signaling and neuronal survival but have currently unclear molecular functions (22).…”
Section: Grb10 Binding Partners Define Its Role In Developmentmentioning
confidence: 99%
“…The gene product is an adapter protein that binds to insulin and insulin-like growth factor receptors inhibiting tyrosine kinase signaling. 39,40 GRB14 − / − mice are lean and have improved insulin sensitivity. The rs3923113 risk allele is associated with reduced insulin sensitivity and T2D in South Asians, indicating a gain of function.…”
Section: Discussionmentioning
confidence: 99%